Cut and paste - Mark Geldof (Bern Open Publishing, 2023)
London, British Library Additional MS 39564 is an anonymous collection of English lessons for the two-hand sword, tentatively dated to the first quarter of the sixteenth century. This manuscript is peculiar in several ways, aside from it being one of only three such texts known to scholars. This paper discusses two aspects of this manuscript that speak to its origins and its survival in its present form. The lessons appear to be out of order and while there is no challenge in rearranging them in a logical fashion, this paper explains why that disorder tells us that Add. MS 39564 is a copy made from loose bi-folds from a now lost exemplar. This also explains the placement of the 'Amen Quod J Ledall' formula between lessons, rather than at the end of the text (where such an attribution is traditionally placed). Finally, this paper explains the significance of that attribution, suggesting it does not identify an original composer or user of the text, only the name of the scribe who produced the unbound sheets that acted as the exemplar for our surviving text. Both of these points remind us that these texts were part of a complicated community of composers, scribes, and readers and that the path of survival is often indirect and meandering.